The implementation of a physical activity intervention in adults with Obstructive Sleep Apnoea over the age of 50 years: a feasibility uncontrolled clinical trial - Julie K. Black; Anna C. Whittaker; Abd A. Tahrani; George M. Balanos (BMC, 2020)
Abstract Background Obstructive Sleep Apnoea (OSA) is a risk factor for cardiovascular disease (CVD) and Type 2 diabetes (T2D). Observational studies suggested that OSA treatment might reduce CVD and T2D but RCTs failed to support these observations in part due to poor adherence to continuous positive airway pressure (CPAP). Physical activity (PA) has been shown to have favourable impact on CVD and the risk of T2D independent of its impact on weight and therefore might provide additional health gains to patients with OSA, whether or not adherent to CPAP. Methods The main aim of this study was to explore the feasibility of providing a 12-week PA intervention to adults aged over 50 with OSA. The secondary aim was to assess the impact of the PA intervention on OSA severity. Patients with moderate-severe OSA (apnoea hypopnea index (AHI) ≥ 15 events/hour (based on overnight ApneaLink™) were recruited in response to posters displayed in workplaces. A 12-week daily PA intervention was delivered in participant's home setting and PA was monitored via text and validated by objective PA measures (GT3X accelerometers). Results The intervention was feasible as all 10 patients (8 males, mean (SD) age 57.3 (6.01)) completed the intervention and PA increased across the 12-weeks. The duration of PA increased from baseline (113.1 min (64.69) per week to study-end following the intervention (248.4 min (148.31) (p = 0.02). Perceived Exertion (RPE) (physical effort) increased significantly between baseline (M = 10.7 (1.94)) to end of intervention (M = 13.8, (1.56) (p < 0.001). The intervention had no significant impact on weight or composition. Following the intervention, there was a statistically non-significant a reduction in AHI from baseline to study end (22.3 (7.35) vs. 15.8 (7.48); p = 0.09). Conclusion It is feasible to deliver a PA intervention to adults aged over 50 with OSA. The intervention resulted in improved PA and AHI levels somewhat and seemingly independent of weight changes. Future trials need to examine whether PA can reduce the burden of OSA associated comorbidities. Trial registration CTN: ISRCTN11016312 Retrospectively Registered 21/07/20.